Vrednotenje površinskih sistemov in izbira premaznega sistema z večkriterijskim odločitvenim modelom - Oblak, Leon (Zbornik gozdarstva in lesarstva, 2005)
The required or expected quality of a coating system depends on the suitable choice of a substrate and a coating system or lining. It is determined with the purpose of use and the expected durability of the product as a whole. If there are no obstacles in evaluating the quality of surface systems (their physical, mechanical and chemical properties), these arise in the final choiceof coating systems. From among many available and qualitatively assessedcoating systems, one has to decide for the best one. The multi-criteria decision-making model is presented herein, that can help solve the problem of choosing the most appropriate coating system from among many alternatives successfully.
Keywords: odločitveni modeli; površinska obdelava; premazi